PENERAPAN MODEL EVALUASI CIPP DALAM MENGEVALUASI PROGRAM LAYANAN PAUD HOLISTIK INTEGRATIF - Petrus Redy Partus Jaya; Felisitas Ndeot (Universitas PGRI Palembang, 2018)
Abstract: This paper aims at designing the evaluation model CIPP in evaluating holistic integrative program services in early childhood education.A description of the terminology evaluation and evaluation of the program be placed on early so that the reader can see the holistic integrative services in early childhood education as a program.Next, elaborated on the model of evaluation of CIPP. An understanding of the four components of the CIPP evaluation be the key to implementing this model in evaluating program services holistic integrative in early childhood education.In the four components of the CIPP evaluation there are a few key questions: